Glycaemia, renal function and body mass in men and women with type 2 diabetes - Marko Pirić; Dunja Šojat; Valentina Mišković; Matej Šapina; Zvonimir Popović; Tatjana Bačun (Medicinski glasnik, 2020)
Aim: To determine parameters of glycaemic control, renal function and anthropometric measurements in patients with type 2 diabetes in family medicine offices and to examine whether there is a difference in these parameters between genders. Methods: This cross-sectional study included 136 patients of both genders diagnosed with type 2 diabetes, with an average age of 69.33±10.87. General and demographic data were collected, anthropometric measurements were taken, as well as data on fasting plasma glucose, HbA 1 c and creatinine level from laboratory findings. Estimated glomerular filtration rate (eGFR) was calculated. Results: The average results of fasting plasma glucose test were 8.43 mmol/L, of HbA1c 7.15%, and of creatinine 79.00 µmol/L. In 19.12% of patients eGFR was <60 mL/min/1.73m 2. 80.15% were overweight and 38.97% had a body mass index (BMI) of 30 kg/ m 2 or higher. Morbid obesity was recorded in 2.94% of patients. Females had a statistically significantly higher hip circumference (p=0.002) and BMI (p=0.019), while males had a statistically significantly higher waist-to-hip ratio (p=0.006) and BMI (p=0.007). Conclusion: The patients did not reach the target value of fasting plasma glucose (<7mmol/L) and HbA1c was above recommended (<7%). Given that the patients were elderly, glucoregulation can be considered as adequate. The average eGFR classified the patients into G2 group (mildly decreased glomerular filtration). The mean BMI was not within the recommended values. It is important to educate patients on a healthy diet and physical activity, to control their weight, but also to choose medications that reduce weight in addition to glycaemic control.
Keywords: blood glucose; body weight; glomerular filtration rate